The Risk of Depressive Symptoms Increases in Radiographic Axial Spondyloarthritis Patients with Acute Anterior Uveitis - Wu, Peiyu; Chen, Zehu; Fang, Xueling; Chen, Yilan; Li, Xuegang (Aktuelle Rheumatologie, 2024)
Background This study aimed to assess the psychological status of radiographic axial spondyloarthritis (r-axSpA) patients with/without acute anterior uveitis (AAU) and to investigate whether the emotional status was different and associated with disease activity and other clinical variables.Patients and Methods This cross-sectional study included a total of 145 r-axSpA in-patients who fulfilled the modified New York criteria for ankylosing spondylitis. AAU was established by ophthalmologists. Clinical variables were collected from patient charts. All patients received a comprehensive rheumatologic assessment for disease activity, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score (ASDAS). The Short Form (SF)-36 Health Survey, the revised Self-Rating Anxiety Scale (SAS) and the revised Self-Rating Depression Scale (SDS) were applied to all participants by psychiatrists.Results Fifty-seven patients were diagnosed as having the first onset of AAU. Compared with the group of r-axSpA without AAU, the risk of depressive symptoms was higher in the group of r-axSpA with AAU (p=0.008). However, there was no significant difference in terms of the risk of anxious symptoms between these groups (p=0.868). In addition, r-axSpA patients with AAU had higher scores of ASDAS-C-reactive protein (ASDAS-CRP) but lower scores of ASDAS-erythrocyte sedimentation rate (ASDAS-ESR) (p=0.032 and p=0.019). Furthermore, there was a negative correlation between SDS scores and duration in r-axSpA patients with AAU. Among all patients, the group of r-axSpA with depressive symptoms had increased CRP levels and ASDAS-CRP scores and lower vitality in SF-36.Conclusion The risk of depressive symptoms increases in r-axSpA patients with AAU. Moreover, r-axSpA patients with uveitis had a higher disease activity as measured by ASDAS-CRP. Physicians should pay more attention to depressive symptoms and AAU in addition to the disease of r-axSpA itself.
Keywords: acute anterior uveitis; disease activity; depressive symptom; radiographic axial spondyloarthritis